Baha Al-Din Al-Qashy's Approach to the Interpretation of the Quranic Surah - Zarnan, Moheb; Youssef , Ismael (Islamic Sciences Journal, 2023)
This research aims to know the method that Bahaa Al-Din Al-Qashi (may Allah have mercy on him) followed in the interpretation of the Qur’anic surahs by collecting and studying what he has mentioned of news and traces in his interpretation. He did not explain the entire Qur’anic surah, but rather he confined himself to transmitting some of the interpretations of the predecessors in the verse or what is related to it. Sometimes he gets the traces that have a direct relationhip with the interprelation of the verse. Other times, he does not transfer any traces that are not related to the interpretation of the verse.This is the most prominent reason that called me to study his method in his book (Al-Mutamad Min Al-Manqul) in general and his method in interpreting the Qur’anic surahs in particular, and I ask God Almighty for payment.